Madrasah Principal Leadership Strategy as a Motor for Developing Teacher Professionalism - Nurlaili, Nurlaili; Asbiri, Asbiri; Sirozi, Muhammad (Journal of Educational Sciences, 2026)
Education as the foundation of national development heavily relies on the quality of professional teachers who continuously develop their competencies, especially in facing the challenges of dynamic curricula and the digital era. Meanwhile, madrasahs, with their unique integration of religious values and general knowledge, require visionary leadership from headmasters to create a conducive work environment that fosters the sustainable improvement of teacher professionalism. This study employs a qualitative method with a literature review approach. The findings reveal that the role of the headmaster as an instructional leader is crucial in enhancing teacher competencies by motivating and facilitating professional development tailored to the teachers' actual needs. Headmasters must also implement leadership strategies that cultivate a supportive, inclusive, and conducive work environment, encouraging teachers to engage in continuous learning and collaboration to improve teaching quality. However, in practice, headmasters face various challenges such as administrative burdens, limited resources, and resistance from teachers that hinder the effectiveness of their roles. Therefore, capacity building in leadership, resource support, and synergy with stakeholders are essential to enable headmasters to optimally and sustainably drive the development of teacher professionalism, ultimately positively impacting the quality of education in madrasahs.